Using personalized mobile technology to enhance reminiscene and cognitive function for alzheimer's disease patient / Anis Hasliza Abu Hashim …[et al.] - Abu Hashim, Anis Hasliza; Mohd Rias, Riaza Perveen; Mohamed, Azlinah; Bustaman, Mek Azura (2014)
The use of mobile technology has been increased rapidly in the past decade. It has been used widely for many purposes and in many different areas. The usage is not only for the purpose of communication, but also for other functions such as in education, healthcare, finance and entertainment industry. This technology is portable and easy to access from any locations. This project is about designing and developing a personalized digital assistant application for an Alzheimer's patient by using mobile and touch screen technologies. The application is aimed to enhance reminiscene and cognitive function of the patient. A prototype is designed to cater the need of the patient, a 63 years old woman who is still new to mobile technology. The patient has difficulties to remember her family members and confuse with her meal times. Findings from this study indicated a good satisfaction level from using the prototype and positive reaction for repetitive use.